Visi, Misi, Tujuan, Dan Strategi Pencapaian Mutu Pendidikan - Makmur Syukri; Rolin Fadilah Hasibuan (Journal on Education, 2024)
A school is an educational institution with a vision, mission, The goals and curriculum are the identity and personality of the school. This Research aims to understand the nature of vision, mission, goals and programs of the two schools, and to determine the alignment of vision and the objectives of the mission as well as the program applied at the two agricultural professional schools. This research method is descriptive – comparative that's quality. The data analysis techniques used were consistent comparison, is the step of comparing the events that can be applied to each type, the integration stages of the types and their characteristics, the stage of determining the theoretical scope and the stage of writing the theory theory. Research results show the relevance of vision, Missions, goals and programs have become ideals or dreams realized in the future school.